Comparative study of cherry varieties used in intense culture - Vaszily, B. (International Journal of Horticultural Science, 2009)
Research in sweet cherry production is intensely stimulated worldwide. The programs started also in Hungary to develop technologies and to find suitable varieties for the purpose of intense cultivation. It means that dimension of crowns should be smaller, with higher number of plants per hectare. Understocks, which let grow the trees slower, are scarce in this species. On the one hand, the braking effect of the respective stocks is insufficient, they get old pretty soon, loose ramification, yield too small fruits and do not comply with the aims of intense cultivation. Experiences prove the necessity of stocks for intense culture, which are vital, growing, easily regenerating, and freely branching. Mahaleb (Prunus mahaleb), a strong growing stock, is still suitable. Further improvement is expected from the contribution of technological elements and the choice of variety. In the present paper, a 9-year old plantation is shown with trees trained to (slender) spindle, and the yield and fruit quality of the year 2009 has been analysed with 6 varieties involved.